PRECISE BORON ISOTOPIC ANALYSIS OF COMPLEX SILICATE (ROCK) SAMPLES USING ALKALI CARBONATE FUSION AND ION-EXCHANGE SEPARATION - Tonarini S.; Pennisi M.; Leeman W.P. (My University, 1997)
We describe a technique for determining the boron isotopic composition of low-B silicate rocks which until recently have been difficult to analyze. The method involves an alkali carbonate fusion for sample dissolution, ion-exchange chromatography for boron purification, and PTIMS analysis using Cs2BO+2. Our procedure combines several previously published methods in a unique manner to simultaneously (1) achieve state-of-the-art precision and accuracy, and (2) expedite analysis with respect to competing methods. Because isotopic fractionation corrections typically are based on concurrent analyses of the SRM-951 boric acid reference standard, these data do not provide a true measure of analytical accuracy or interlaboratory biases. In this study, analytical precision and accuracy were evaluated independently through replicate analyses of the JB-2 basalt reference standard, with completely independent chemical extractions of boron in each case. The average corrected 11B10B ratio obtained is 4.0728 +/- 0.0019 (2σ external uncertainty), which corresponds to a δ11B value of +7.23 +/- 0.47%%. This result agrees closely with data obtained by Nakamura et al. [Nakamura, E., Ishikawa, T., Birck, J.L., Allegre, C., 1992. Precise boron isotopic analysis of natural rock samples using a boron-mannitol complex. Chem. Geol. 94, 193-204.] using the HF digestion method. We strongly recommend that JB-2 be analyzed routinely in future boron isotopic studies to facilitate assessment of analytical uncertainties and interlaboratory biases.
Keywords: BORON; ISOTOPES; GEOCHEMISTRY; MASS SPECTROMETRY; STANDARDS